A study of factors influencing the water absorption capacity of Canadian hard red winter wheat flour. (May 2018) - Sapirstein, Harry; Wu, Yao; Koksel, Filiz; Graf, Robert
Abstract: The nature of variation in water absorption capacity in Canadian hard red winter (HRW) wheat genotypes was studied. Wheat and flour were evaluated for a range of physical and chemical properties including hardness indices, protein content, total and water-extractable arabinoxylan (WEAX) contents and flour particle size by laser diffraction. Absorption, as measured by farinograph (FA) ranged from 54 to 66%. The most highly correlated conventional parameters to FA were protein and WEAX contents, particle size index and starch damage, with correlations ranging from r = 0.37 to 0.56 in absolute values. The volume fractions of large and small flour particles had the highest correlations to FA (r∼0.67). Multivariate regression analysis produced 3 or 4 variable models of FA prediction with R 2 ranging from 0.64 to 0.95, depending on the sample population. Results indicated that FA is a complex quality parameter with low values attributable to one or more of low levels of wheat hardness, protein content or AX content, depending on genotype. Improving FA in HRW wheat consistent with hard spring wheat appears to be feasible by increasing concentration of deficient parameters by breeding, especially WEAX which has high heritability and ample variation in the HRW wheat germplasm that was studied. Highlights: Grain hardness, protein and AX contents, flour particle size all affect absorption. No single wheat or flour parameter was strongly related to absorption. Absorption was associated with volume fraction of large and small flour particles. Breeding HRW wheats with higher WE-AX content should improve absorption.